enow.com Web Search

Search results

  1. Results from the WOW.Com Content Network
  2. Expression (mathematics) - Wikipedia

    en.wikipedia.org/wiki/Expression_(mathematics)

    The same syntactic expression 1 + 2 × 3 can have different values (mathematically 7, but also 9), depending on the order of operations implied by the context (See also Operations § Calculators). For real numbers , the product a × b × c {\displaystyle a\times b\times c} is unambiguous because ( a × b ) × c = a × ( b × c ) {\displaystyle ...

  3. Elementary algebra - Wikipedia

    en.wikipedia.org/wiki/Elementary_algebra

    If x and y are integers, rationals, or real numbers, then xy = 0 implies x = 0 or y = 0. Consider abc = 0. Then, substituting a for x and bc for y, we learn a = 0 or bc = 0. Then we can substitute again, letting x = b and y = c, to show that if bc = 0 then b = 0 or c = 0. Therefore, if abc = 0, then a = 0 or (b = 0 or c = 0), so abc = 0 implies ...

  4. Algebraic expression - Wikipedia

    en.wikipedia.org/wiki/Algebraic_expression

    [1] [2] [3] [better source needed]. For example, ⁠ 3 x 22 x y + c {\displaystyle 3x^{2}-2xy+c} ⁠ is an algebraic expression. Since taking the square root is the same as raising to the power ⁠ 1 / 2 ⁠ , the following is also an algebraic expression:

  5. Polynomial - Wikipedia

    en.wikipedia.org/wiki/Polynomial

    For example, antiderivatives of x 2 + 1 have the form ⁠ 1 / 3x 3 + x + c. For polynomials whose coefficients come from more abstract settings (for example, if the coefficients are integers modulo some prime number p , or elements of an arbitrary ring), the formula for the derivative can still be interpreted formally, with the coefficient ...

  6. Binomial theorem - Wikipedia

    en.wikipedia.org/wiki/Binomial_theorem

    In elementary algebra, the binomial theorem (or binomial expansion) describes the algebraic expansion of powers of a binomial.According to the theorem, the power ⁠ (+) ⁠ expands into a polynomial with terms of the form ⁠ ⁠, where the exponents ⁠ ⁠ and ⁠ ⁠ are nonnegative integers satisfying ⁠ + = ⁠ and the coefficient ⁠ ⁠ of each term is a specific positive integer ...

  7. Algebra - Wikipedia

    en.wikipedia.org/wiki/Algebra

    For statements with several variables, substitution is a common technique to replace one variable with an equivalent expression that does not use this variable. For example, if one knows that y = 3 x {\displaystyle y=3x} then one can simplify the expression 7 x y {\displaystyle 7xy} to arrive at 21 x 2 {\displaystyle 21x^{2}} .

  8. Equation - Wikipedia

    en.wikipedia.org/wiki/Equation

    The solutions –1 and 2 of the polynomial equation x 2x + 2 = 0 are the points where the graph of the quadratic function y = x 2x + 2 cuts the x-axis. In general, an algebraic equation or polynomial equation is an equation of the form =, or = [a]

  9. Polynomial expansion - Wikipedia

    en.wikipedia.org/wiki/Polynomial_expansion

    In mathematics, an expansion of a product of sums expresses it as a sum of products by using the fact that multiplication distributes over addition. Expansion of a polynomial expression can be obtained by repeatedly replacing subexpressions that multiply two other subexpressions, at least one of which is an addition, by the equivalent sum of products, continuing until the expression becomes a ...